O processo de construção do PPPQ da escola quilombola Fernando Nunes Rodrigues - LIMA, Marciele Nascimento de (2023)
The article has as its theme “The construction process of the PPPQ of the Fernando Nunes Rodrigues Quilombola School”. The research problem is: How was the School's PPPQ built taking into account the dialogue of the remaining community in order to meet what the Laws determine? General objective: Reflect what PPPQ is in the conception of the authors and actors of the school. The methodological approach guided a field research in a bibliographical, descriptive and documental way, with content analysis and data treatment in a qualitative way. Approached authors: Alves (1992); Amaral (2008); Arroyo (2013); Ferreira (1975); Marçal (2001); Marks (1990); Sacristan (2017); Vasconcelos (1999); Veiga (1992/2013a/b); and Vergara (2007). The results of the investigation indicate that it was possible to deepen the subject with authors and the law that guarantees the quilombola teaching, as well as it allowed me to understand that the PPPQ was built even with little participation of the school teachers. However, it took into account the dialogue of the remaining community collectively in an attempt to require appropriate means to carry out its intentionality, capable of affecting lives, knowledge, actions, culture and knowledge; and the laws in force so that the pedagogical practices legitimize the history, the local culture, the way of life of the quilombola community of which the school is a part. And yet, it allowed me a significant learning and understanding that laws alone, even contemplated in a PPPQ do not guarantee that Afro-Brazilian History and Culture is effectively worked in classes, but it is a challenge and responsibility of professionals to do so.